Never have your dog stuffed eaudiobook And other things i've learned. - Alda, Alan (Random House Audio, 2005)
He’s one of America’s most recognizable and acclaimed actors–a star on Broadway, an Oscar nominee for The Aviator, and the only person to ever win Emmys for acting, writing, and directing, during his eleven years on M*A*S*H. Now Alan Alda has written a memoir as elegant, funny, and affecting as his greatest performances. “My mother didn’t try to stab my father until I was six,” begins Alda’s irresistible story. The son of a popular actor and a loving but mentally ill mother, he spent his early childhood backstage in the erotic and comic world of burlesque and went on, after early struggles, to achieve extraordinary success in his profession. Yet Never Have Your Dog Stuffed is not a memoir of show-business ups and downs. It is a moving and funny story of a boy growing into a man who then realizes he has only just begun to grow. It is the story of turning points in Alda’s life, events that would make him what he is–if only he could survive them. From the moment as a boy when his dead dog is returned from the taxidermist’s shop with a hideous expression on his face, and he learns that death can’t be undone, to the decades-long effort to find compassion for the mother he lived with but never knew, to his acceptance of his father, both personally and professionally, Alda learns the hard way that change, uncertainty, and transformation are what life is made of, and true happiness is found in embracing them. Never Have Your Dog Stuffed , filled with curiosity about nature, good humor, and honesty, is the crowning achievement of an actor, author, and director, but surprisingly, it is the story of a life more filled with turbulence and laughter than any Alda has ever played on the stage or screen.